All Days 2013
DOI: 10.2118/163608-ms
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning for Efficiently Applying Algebraic Multigrid in Fully Implicit Reservoir Simulations

Abstract: Fully implicit petroleum reservoir simulations result in huge, often very ill-conditioned linear systems of equations to solve for different unknowns, for example, pressure and saturations. It is well known that the full system matrix contains both hyperbolic as well as nearly elliptic sub-systems. Since the solution of the coupled system is mainly determined by the solution of their elliptic (typically pressure) components, (CPR-type) two-stage preconditioning methods still belong to the most popular approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Also, the unified initialization interface of AMGCL building blocks means it is easy to reuse existing functionality in order to come up with new preconditioning techniques. Notable examples included into the library codebase are CPR [21] and Schur complement pressure correction [20,35] preconditioners. CPR works best in fully implicit black-oil simulations, and Schur complement pressure correction is well-suited for Navier-Stokes-like problems.…”
Section: Extensibilitymentioning
confidence: 99%
“…Also, the unified initialization interface of AMGCL building blocks means it is easy to reuse existing functionality in order to come up with new preconditioning techniques. Notable examples included into the library codebase are CPR [21] and Schur complement pressure correction [20,35] preconditioners. CPR works best in fully implicit black-oil simulations, and Schur complement pressure correction is well-suited for Navier-Stokes-like problems.…”
Section: Extensibilitymentioning
confidence: 99%
“…The constrained pressure residual (CPR) preconditioner is widely used in the community of reservoir simulation [15,38]. This is based on subblocks of the Jacobian matrix and uses an approximate pressure solve such as algebraic multigrid (AMG) [25] to constrain the residual of the full system, and thus is known as a physics-splitting approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, CPR-AMG may not work well when some source terms corresponding to complex physics destroy the elliptic properties exploited by AMG. In addition, the decoupling process tends to cause a conflict between the convergence of AMG and the convergence of the outer CPR iteration [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the second stage an ILU process is applied onto the updated global system. Empirically, it is observed that the computational complexity of AMG-CPR scales as O (N ␣ ) with 1 Յ ␣ Յ 1.5, where N is the total number of degrees of freedom in the system (Gries et al (2004); Masson et al (2004); Lacroix et al (2003); Stuben (2001)). Combined with the computational costs of the residual and Jacobian matrix evaluation and the thermodynamics, the overall complexity of a nonlinear iteration is generally superlinear in N.…”
Section: Introductionmentioning
confidence: 99%